ChemInform Abstract: Gold Vinylidene Complexes. Intermolecular C(sp3)—H Insertions and Cyclopropanations Pathway. Issue 12 (14th March 2013) - Hashmi, A. Stephen K.; Wieteck, Marcel; Braun, Ingo; Rudolph, Matthias; Rominger, Frank
Abstract Cyclization of diyne (II) in the presence of gold complexes (Ia)/(Ib) results in formation of a highly reactive vinylidene intermediate which is treated with alkenes to yield a series of annulated ring systems containing a cyclobutane moiety.